Biological Sex: A Potential Moderator of Physical Activity Efficacy on Brain Health - Barha, Cindy K.; Hsu, Chun-Liang; ten Brinke, Lisanne; Liu-Ambrose, Teresa (Frontiers in Aging Neuroscience, 2019)
The number of older persons worldwide living with cognitive impairment and neurodegenerative diseases is growing at an unprecedented rate. Despite accumulating evidence that engaging in physical activity is a promising primary behavioural strategy to delay or avert the deleterious effects of aging on brain health, a large degree of variation exists in study findings. Thus before physical activity and exercise can be prescribed as “medicine” for promoting brain health, it is imperative to understand how different biological factors can attenuate or amplify the effects of physical activity on cognition at the individual level. In this mini-review, we briefly discuss the current state of the literature examining the relationship between physical activity and brain health in older adults and we present the argument that biological sex is a potent moderator of this relationship. Additionally, we highlight some of the potential neurobiological mechanisms underlying this sex difference for this relatively new and rapidly expanding line of research.